River discharge and tidal height data in the Changjiang Estuary in January 2017 and August 2016 - Guo, Leicheng (PANGAEA, 2020)
This dataset contains tidal height in the Changjiang River estuary in August of 2016 and January 2017, which represent the wet (high river flow) and dry (low river discharge) seasons respectively. The data are collected from the hydrology bureau of the water resource department of the state governments in China (http://yc.wswj.net/ahsxx/LOL/public/public.html; http://221.226.28.67:88/jsswxxSSI/Web/Default.html?m=2). The tidal height data are measured using the traditional method of poles. All data are referenced to the Wusong height datum, which is ~2 m below the local mean sea level. The position of the gauge sites are referred to the data information file. The data are used in the paper published in Geophysical Research Letters (Guo et al., 2020, Strong inland propagation of low-frequency long waves in river estuaries).
Keywords: Changjiang; tidal height